Case Report: Adult Right-Sided Bochdalek Hernia Complicated by Intrathoracic Bowel Perforation - Ramspott, Jan Philipp; Regenbogen, Stephan; Jäger, Tarkan; Lechner, Michael; Mayer, Franz; Gabersek, Ana; Emmanuel, Klaus; Schredl, Philipp (Frontiers in Surgery, 2021)
Right-sided Bochdalek hernia is a mostly congenital condition of the diaphragm caused by a persistence of the pleuroperitoneal cavity and a rare disease in adults. As it often presents as an emergent situation, urgent diagnostics and surgical intervention are essential to reduce morbidity and mortality rates. Choosing the right surgical approach (abdominal, thoracic, or a combination of both) can be very challenging for clinicians. Here, we report a case of a 40-year-old woman, who presented with severe abdominal pain and tachypnoea. Imaging revealed a right-sided Bochdalek hernia. Emergency laparotomy was performed followed by reduction of hernia content, right-sided hemicolectomy, and side-to-side anastomosis from the ileum to the transverse colon due to intestinal ischemia and intrathoracic bowel perforation. The postoperative course was complicated by a pleural empyema. Therefore, the patient underwent thoracotomy. One year after surgical repair the patient had no recurrence. Here, we discuss feasible approaches for the surgical management of complicated Bochdalek hernias.